The readability of a high stakes Physics examination paper - Umesh Ramnarain (Acta Academica, 2012)
This article reports on the readability of a Physics examination paper written by grade-12 students. A sample of 500 scripts was analysed for readability problems associated with linguistic features synonymous with scientific writing. The study revealed that where a question displayed a linguistic feature of scientific writing, this contributed to students doing an incorrect calculation, focusing on the wrong aspect of the question, repeating a segment of a question, and misinterpreting a word or a phrase. In view of these findings, the article argues that greater attention needs to be paid to the language of science in the classroom.